2019
DOI: 10.1002/jcp.28162
|View full text |Cite
|
Sign up to set email alerts
|

Silencing MEKK3 attenuates cardiomyocyte injury caused by hypoxia/reoxygenation via the sonic hedgehog pathway

Abstract: MEKK3 is a member of MAP3K, which plays a pivotal role in cardiac diseases. In this study, we aimed to investigate the effects and potential mechanisms of MEKK3 on hypoxia/reoxygenation (H/R) injury of cardiomyocytes. After exposing H9C2 cells to H/R insult, real‐time polymerase chain reaction and western blot analysis showed that MEKK3 was highly expressed. Cell viability, cell apoptosis, caspase 3/7 activity, and cleaved‐caspase 3 expression were tested using a CCK‐8 assay, Cell Death Detection PLUS ELISA, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…5 It has indicated that ischemia-induced hypoxia and reoxygenation (H/R) were related to apoptosis, production of reactive oxygen species, inflammation, and so on. 6,7 However, the mechanism of myocardial ischemia remains ill-defined. Therefore, it is important to figure out potential mechanisms of action to develop novel therapeutic regimen for myocardial ischemia injury.…”
Section: Introductionmentioning
confidence: 99%
“…5 It has indicated that ischemia-induced hypoxia and reoxygenation (H/R) were related to apoptosis, production of reactive oxygen species, inflammation, and so on. 6,7 However, the mechanism of myocardial ischemia remains ill-defined. Therefore, it is important to figure out potential mechanisms of action to develop novel therapeutic regimen for myocardial ischemia injury.…”
Section: Introductionmentioning
confidence: 99%
“…Beas-2B and NHBE cells were plated into 96-well plates and pretreated for 2 h with 1, 5 and 10 μM ALT and then treated with 5% CSE for 24 h. Caspase-3 activity was measured by using caspase-Glo 3/7 Assay (Promega, Madison, WI, USA) kit in accordance with a previous report and the manufacturer's instructions [23]. Capase-Glo 3/7 Reagent (100 μL) was added to cells for another 2 h at room temperature and the luminescence intensity was recorded at 570 nm by using a microplate reader.…”
Section: Caspase-3 Activitymentioning
confidence: 99%
“…MAP3K3 knockdown blocked mitochondrial impairment by inhibiting the loss of mitochondrial membrane potential and cytochrome C expression as well as promoting ATP synthesis and reduced apoptosis and mitochondrial damage in cardiomyocytes in response to hypoxia/reoxygenation (H/R). 34 MAP3K3 deficiency also increased the life span in Caenorhabditis elegans and decreased the levels of ROS. 71 In the current study, we also found that MAP3K3 knockdown reduced apoptosis and senescence markers in ECs responding to H 2 O 2 through the MAPK signaling pathway (Figure 6A-D).…”
Section: Discussionmentioning
confidence: 93%
“…31,32 Some studies demonstrate key effects of MAP3K3 in apoptosis and senescence in diverse cell types. 14,[33][34][35][36] In this study, we identify that miR-181b regulates endothelial aging by modulating the MAPK signaling pathway. We explore the mechanistic basis for miR-181b regulation of apoptosis and senescence in ECs that is dependent on a MAP3K3/MAPK signaling cascade.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation